Synthesis of fluorescent analogs of relaxin family peptides and their preliminary in vitro and in vivo characterization - Chan, Linda; Smith, Craig; Chua, Berenice; Lin, Feng; Bathgate, Ross; Separovic, Frances; Gundlach, Andrew; Hossain, M. Akhter; Wade, John (Frontiers in Chemistry, 2013)
Relaxin, a heterodimeric polypeptide hormone, is a key regulator of collagen metabolism and multiple vascular control pathways in humans and rodents. Its actions are mediated via its cognate G-protein-coupled receptor, RXFP1 although it also ‘pharmacologically’ activates RXFP2, the receptor for the related, insulin-like peptide 3 (INSL3), which has specific actions on reproduction and bone metabolism. Therefore, experimental tools to facilitate insights into the distinct biological actions of relaxin and INSL3 are required, particularly for studies of tissues containing both RXFP1 and RXFP2. Here, we chemically functionalized human (H2) relaxin, the RXFP1-selective relaxin analogue H2:A(4-24)(F23A), and INSL3 to accommodate a fluorophore without marked reduction in binding or activation propensity. Chemical synthesis of the two chains for each peptide was followed by sequential regioselective formation of their three disulfide bonds. Click chemistry conjugation of Cy5.5 at the B-chain N-terminus, with conservation of the disulfide bonds, yielded the analogues displaying appropriate selective binding affinity and ability to activate RXFP1 and/or RXFP2 in vitro. The in vivo biological activity of Cy5.5-H2 relaxin and Cy5.5-H2:A(4-24)(F23A) was confirmed in mice, as acute icv infusion of these peptides (but not Cy5.5-INSL3) stimulated water drinking, an established behavioral response elicited by central RXFP1 activation. The central distribution of Cy5.5-conjugated peptides was examined in mice killed 30 min after infusion, revealing fluorescence within brain tissue near-adjacent to the cerebral ventricle walls relative to deeper brain areas. These data will aid the interpretation of behavioral studies. Production of fluorophore-conjugated relaxin family peptides will facilitate future pharmacological studies to probe the function of H2 relaxin/RXFP1 and INSL3/RXFP2 signaling in vivo while tracking their distribution following central or peripheral administration.